1987
DOI: 10.1111/j.1545-5300.1987.00461.x
|View full text |Cite
|
Sign up to set email alerts
|

The Family Rorschach with Families of Schizophrenics: Replication and Extension

Abstract: Using a modified version of procedures outlined by Shapiro and Wild (9), this study evaluates the use of a Family Rorschach technique as a means of distinguishing families of schizophrenic patients from those of psychiatrically hospitalized, nonschizophrenic individuals. The patients were diagnosed using Research Diagnostic Criteria, and families were matched for age, intelligence, and socioeconomic characteristics. Results showed that the families with schizophrenic offspring scored significantly lower (that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1989
1989
1996
1996

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…Put simply, confusing and disorienting styles of parental communication are reflected in the confused and disoriented thought processes of schizophrenic offspring. Related studies have shown that offsprings' and spouses' performance of cognitive tasks in an experimental situation is impaired during and immediately following interactions filled with high CD-type communication (Blakar, 1981;Carter, Robertson, Ladd & Alpert, 1987;Mossige, Petterson & Blakar, 1979;Reiss, 1981;Rund, 1986;Shapiro & Wild, 1976;Solvberg & Blakar, 1975). Lastly, Waxler (1974) found that schizophrenic offsprings' performance on a cognitive task improved after interaction with normal offsprings' parents (who presumably were low in CD).…”
Section: Studies Of Communication Deviance and Adult Thought Disordersmentioning
confidence: 98%
“…Put simply, confusing and disorienting styles of parental communication are reflected in the confused and disoriented thought processes of schizophrenic offspring. Related studies have shown that offsprings' and spouses' performance of cognitive tasks in an experimental situation is impaired during and immediately following interactions filled with high CD-type communication (Blakar, 1981;Carter, Robertson, Ladd & Alpert, 1987;Mossige, Petterson & Blakar, 1979;Reiss, 1981;Rund, 1986;Shapiro & Wild, 1976;Solvberg & Blakar, 1975). Lastly, Waxler (1974) found that schizophrenic offsprings' performance on a cognitive task improved after interaction with normal offsprings' parents (who presumably were low in CD).…”
Section: Studies Of Communication Deviance and Adult Thought Disordersmentioning
confidence: 98%
“…Whereas families with normal offspring were typically able to achieve consensus and collectively report a moderately detailed percept, the written responses of members of families with schizophrenic offspring included a great deal of vagueness and disagreement with one another, reflecting tendencies toward pseudomutuality and premature closure. Carter, Robertson, Ladd, and Alpert (2), replicating Shapiro and Wild's study, later reported significant differences between families of schizophrenics and families of hospitalized but nonschizophrenic offspring, evidence indicating that the communication deviance was not simply a family response to the stress associated with having a family member hospitalized.…”
mentioning
confidence: 69%
“…In this task, family members attempt to reach a consensus on their perceptions of the inkblots. Using this procedure, several investigators have found that they could clearly differentiate families with a schizophrenic member from control families, and that families with schizophrenic members exhibit significantly more communication and attentional problems than families with non-schizophrenic offspring (1,2,9,16,27).…”
Section: Communication Deviance (Cd) Refers To Confusing and Fragmentmentioning
confidence: 99%